Intraocular pressure changes following small-incision cataract surgeries in a tertiary care center: a prospective study - Leena M Varghese; Vidya Hegde; Sumi Lukose (Delta Journal of Ophthalmology, 2023)
Aim This study aims to identify the pattern of intraocular pressure (IOP) changes after uneventful small-incision cataract surgery (SICS) in previously normotensive eyes, to know the cause for these postoperative changes, and to correlate the preoperative anterior chamber depth (ACD) to the postoperative IOP change. Patients and methods A prospective study was conducted at Yenepoya Medical College, Mangalore, India on 87 non-glaucomatous eyes that underwent an uneventful SICS with posterior chamber intraocular lens implantation. The IOP was measured preoperatively and postoperatively on days 1, 3, and weeks 1, 3, and 6. We tried to identify the cause of the IOP change. The preoperative and postoperative ACD change was also noted and correlated with the IOP change. Results The mean preoperative IOP was 14±1.81 mm Hg. On the first postoperative day (POD-1), 54% of the eyes showed a statistically significant rise in IOP (mean IOP=17.03±7.17 mm Hg, P=0.0002), and 28% showed a mean fall in IOP of 9.28 mm Hg. On the third postoperative day (POD-3), the IOP showed a statistically significant rise (14.82±3.93 mm Hg, P=0.028) compared with the preoperative value. At the end of the first postoperative week (POW-1), the IOP showed a statistically nonsignificant rise (P=0.66). By the third postoperative week (POW-3), the IOP decreased to 13.82±2.83 mm Hg, with a statistically nonsignificant difference compared with the preoperative IOP (P=0.45). However, there was a statistically significant decrease in the IOP (P=0.0001) in the sixth postoperative week (POW-6). Postoperatively, there was a statistically significant increase in ACD from 3.01±0.31 to 3.23±0.36 mm (P=0.0001) by the POW-3. The preoperative ACD showed a statistically significant moderate negative correlation with late postoperative IOP (r=−0.7394, P<0.0001). Conclusion After SICS, at the end of 6 weeks, there was a statistically significant decrease in the mean IOP with an increase in the ACD. A moderate negative correlation existed between the preoperative ACD and late postoperative IOP. It was found that 2.3% of the eyes were steroid responders and showed a rise in IOP at POW-3.